Strategic orientation influence on SMEs export performance in Nigeria: measurement validation and preliminary analysis - Abubakar, Mukhtar Salisu; Abdul Rahim, Norhuda; Raja Yusof, Raja Nerina; Yahya, Mohamed Hisham (Universiti Utara Malaysia Press, 2024)
This research is aimed at enhancing comprehension and validation of the variables that drive the export performance of small and medium enterprises (SMEs) in Nigeria. Notwithstanding the paucity of evidence regarding the export experiences of SMEs from developing countries in the literature, studying the SME setting is crucial, given its growing significance in enhancing national and global economies. A survey design was used to gather data from owners and managers of Nigerian SMEs that were involved in exports. Based on convenience sampling, 450 questionnaires were distributed. Of this number, 278 valid responses were returned. The study model was assessed via partial least square structural equation modelling (PLS-SEM), and the statistical package for social science (SPSS v24) was used for preliminary analysis. The results seem to suggest that the seven-construct measurements—entrepreneurial orientation, market orientation, learning orientation, export orientation, export knowledge, access to finance, and export performance—are well suited for estimating the variables under investigation in a Nigerian setting. Similarly, the direct relationship between the exogenous and endogenous constructs was positive and significant. The outcomes validated applying the dynamic capability view and its principles to explain the success of the export performance of SMEs in Nigeria.